The rise of the 'Instagram economy' phenomenon in a South African context : An exploration of how conspicuous consumption on Instagram contributes to brand value creation - Kleintjes, Alyssa (Centre for Film and Media Studies, 2018)
The number of brands using Instagram as a branding tool is steadily rising and so too is the rate of brand related consumer Interactions on social media. The sociocultural shifts in behavioural norms on Instagram have facilitated an increase in social word-of mouth that is surpassing traditional media advertising as the primary influence on consumers' purchase decisions. This revolution in Instagram marketing has facilitated the development of the Instagram Economy. This research aims to draw actionable insights into the South African Instagram Economy, which brand managers can use to inform their Instagram marketing strategies in order to leverage the economic capabilities of this platform. In order to draw actionable insights the study focused on each of the three main role players of the Instagram Economy: brands, Instagram influencers and consumers. The method of research for each of these three components of study was: a case study of a brand Instagram account, a quantitative content analysis of Instagram influencers' brand sponsored posts and lastly a closed, fixed response consumer questionnaire which prospective respondents could voluntarily participate in. This research identified that in order to develop successful brand presence on Instagram and increase the rate of brand related Instagram interactions that influence consumer purchase decisions, brands need to develop the right content for their target audience, partner with influencers that match the brand's values and know their audience's Instagram usage habits in order to reach them effectively.